Stratified Taylor–Green vortex by lattice Boltzmann methods: Influence of stencils, forcing schemes, and collision models. (30th April 2023) - Wilde, Dominik; Nidhan, Sheel; Pham, Hieu T.; Foysi, Holger; Reith, Dirk; Sarkar, Sutanu
Abstract: Stably stratified Taylor–Green vortex simulations are performed by lattice Boltzmann methods (LBM) and compared to other recent works using Navier–Stokes solvers. The density variation is modeled with a separate distribution function in addition to the particle distribution function modeling the flow physics. Different stencils, forcing schemes, and collision models are tested and assessed. The overall agreement of the lattice Boltzmann solutions with reference solutions from other works is very good, even when no explicit subgrid model is used, but the quality depends on the LBM setup. Although the LBM forcing scheme is not decisive for the quality of the solution, the choice of the collision model and of the stencil are crucial for adequate solutions in underresolved conditions. The LBM simulations confirm the suppression of vertical flow motion for decreasing initial Froude numbers. To gain further insight into buoyancy effects, energy decay, dissipation rates, and flux coefficients are evaluated using the LBM model for various Froude numbers. Graphical abstract: Highlights: Stably stratified Taylor–Green vortex by lattice Boltzmann methods (LBM). Description of the LBM for stably stratified flows with periodic boundaries. Assessment of LBM forcing schemes, collision models, and stencils. Different Froude numbers are tested and flux coefficients are measured.